Analisis Yuridis Terhadap Tindak Pidana Penggunaan Ijazah Palsu: Studi Putusan Nomor 1583/Pid.Sus/2021/PT. MDN - Simbolon, Herti Noita; Nababan, Ramsul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
A diploma is a letter of completion of study given to students who have successfully completed and taken a certain level of education. The levels of education are Elementary School (SD), Middle School (SMP), High School (SMA), and College. This diploma is used for various needs, one of which is to find work. However, along with the development of technology, many frauds have arisen such as forgery and the use of fake diplomas. Using a fake diploma is clearly a criminal offense because it is regulated in law. There are many types of misuse of fake diplomas in Indonesia that have been revealed and those that have not yet been revealed. This research aims to find out how the case sat and the basis for the judge's considerations in decision Number 1583/Pid.Sus/2021/PT. MDN. This research uses a type of normative juridical research using secondary data sources. Data collection techniques in research use library research. In normative juridical research, library research is used to collect legal materials or secondary data. The results of the research show that the judge in handing down a criminal decision against the defendant Suhardi, whose decision strengthened the Sei Rempah District Court Decision No. 328/Pid.Sus/2021/PN Srh because it has fulfilled the elements in article 69 of Law no. 20 of 2003 concerning the National Education System. The considerations in handing down this decision are correct, which can be seen from the public prosecutor's demands, the indictment, the public prosecutor's demands, the evidence at trial based on evidence, and the appeal file.